The Reasons to Go On Living Project: stories of recovery after a suicide attempt. Issue 3 (3rd July 2017) - Chan, K. Jacky; Kirkpatrick, Helen; Brasch, Jennifer
ABSTRACT: Qualitative research in suicidology has become increasingly common in the literature. Lakeman and FitzGerald (2008) conducted a review of qualitative works specifically on suicide and recovery. Five interconnected themes—suffering/psychache, struggle, connection, turning points, and suicide and coping—were identified. The Reasons to Go On Living Project (RTGOL) project was a web-based narrative research project that sought to understand the transition from making a suicide attempt to choosing life. This article reports the findings of a secondary analysis of the narratives. By using Lakeman and FitzGerald's themes as a starting point, one hundred and thirteen submissions were thematically analyzed using a deductive approach. The findings are mostly consistent with the interconnected themes identified by Lakeman and FitzGerald. Moreover, subthemes were identified to better reflect the lived experience of the participants. Clinical and research implications of this project will be discussed.